Small-firm formation in biotechnology a comparison of France, Britain and Canada - Walsh, Vivien (Technovation)
A comparison is made between the newly emerging dedicated biotechnology firms (DBFs) in France, Britain and Canada and their somewhat longer established counterparts in the USA where larger investments are available from Government for fundamental research.